Trypanosoma cruzi serinecarboxipeptidaseis a sufated glycoprotein and a minor antigen in human Chagas disease infection - Soprano, Luciana L. (2017)
In this work, the presence of sulfated N-glycans was studied in a high-mannose-type glycoprotein of Trypanosoma cruzi with serinecarboxipeptidase (TcSCP) activity. The immune cross-reactivity between purified SCP and Cruzipain (Cz) was evidenced using rabbit sera specific for both glycoproteins. Taking advantage that SCP co-purifies with Cz from Concanavalin-A affinity columns, the Cz–SCP mixture was desulfated, ascribing the cross-reactivity to the presence of sulfate groups in both molecules. Therefore, knowing that Cz is a sulfated glycoprotein, with antigenic sulfated epitopes (sulfotopes), SCP was excised from SDS-PAGE and the N-glycosydic chains were analyzed by UV–MALDI–TOF-MS, confirming the presence of short-sulfated high-mannose-type oligosaccharidic chains. Besides, the presence of sulfotopes was analyzed in lysates of the different parasite stages demonstrating that a band with apparent molecular weight similar to SCP was highly recognized in trypomastigotes. In addition, SCP was confronted with sera of infected people with different degrees of cardiac dysfunction. Although most sera recognized it in different groups, no statistical association was found between sera antibodies specific for SCP and the severity of the disease. In summary, our findings demonstrate (1) the presence of sulfate groups in the N-glycosidic short chains of native TcSCP, (2) the existence of immune cross-reactivity between Cz and SCP, purified from epimastigotes, (3) the presence of common sulfotopes between both parasite glycoproteins, and (4) the enhanced presence of sulfotopes in trypomastigotes, probably involved in parasite–host relationship and/or infection. Interestingly, we show for the first time that SCP is a minor antigen recognized by most of chronic Chagas disease patient’s sera.